(Re)Producing Family: Women Surviving the Holocaust - Abramson, Zelda (Atlantis, 2007)
This paper explores women's survival strategies in concentration camps through a series of interviews with women Holocaust survivors. There are three prevalent themes that weave through this paper: stories of individual survival; stories of collective survival; and the reproduction of family.